Neuro-affirmative support for autism, the Double Empathy Problem and monotropism - Brosnan, Mark; Camilleri, Louis John (Frontiers in Psychiatry, 2025)
Conceptualising autism within a neurodiversity approach raises fundamental questions regarding the nature of the goals pursued in autism support and who is responsible for achieving these goals. The Double Empathy Problem considers deficits in social communication as residing between autistic and non-autistic communicators, rather than solely within the autistic individual. This is important as autistic individuals can have different perceptions of what appropriate goals for autism support should be, when compared to (non-autistic) family, friends and professionals. Monotropism highlights the importance of engaging with the interests of the autistic individual when considering support. This perspective considers the extent to which autistic individuals can self-set and self-achieve autism support goals? Social narratives have a specific goal and explicit description of how to achieve this goal and what the outcome of achieving the goal will be. The Stories Online For Autism app (SOFA-app.com) develops and delivers social narratives for autistic individuals. The SOFA-app has proven to be highly acceptable and effective in supporting autistic individuals. Initially our research focussed on family, friends and professionals developing autism support for autistic children. Subsequently we extended this methodology to explore the self-set goals of autistic adults and children as well as capacity to self-achieve these goals successfully. Digital support for the development and delivery of social narratives to support self-set goals for autistic individuals is recommended. Addressing the Double Empathy Problem and supporting self-set goals are also considered alongside the implications of preferences associated with Monotropism to argue this approach can be considered neuro-affirmative.